Invasion of Human Oral Epithelial Cells by Prevotella intermedia - Dorn, Brian R. (American Society for Microbiology, 1998)
Invasion of oral epithelial cells by pathogenic oral bacteria may represent an important virulence factor in the progression of periodontal disease. Here we report that a clinical isolate of Prevotella intermedia, strain 17, was found to invade a human oral epithelial cell line (KB), whereas P. intermedia 27, another clinical isolate, and P. intermedia 25611, the type strain, were not found to invade the cell line. Invasion was quantified by the recovery of viable bacteria following a standard antibiotic protection assay and observed by electron microscopy. Cytochalasin D, cycloheximide, monodansylcadaverine, and low temperature (4°C) inhibited the internalization of P. intermedia 17. Antibodies raised against P. intermedia type C fimbriae and against whole cells inhibited invasion, but the anti-type-C-fimbria antibody inhibited invasion to a greater extent than the anti-whole-cell antibody. This work provides evidence that at least one strain of P. intermedia can invade an oral epithelial cell line and that the type C fimbriae and a cytoskeletal rearrangement are required for this invasion.